ORIGINAL PAPEREndocrine disorders in children with craniopharyngiomas during the preoperative period - Stawerska, Renata; Zakrzewski, Krzysztof; Polis, Bartosz; Hilczer, Maciej; Smyczyńska, Joanna; Kobielski, Artur; Polis, Lech; Lewiński, Andrzej (Archives of Medical Science, 2005)
Introduction: The aim of the study was an assessment of the type and incidence of endocrine disorders against the background of general, neurological and ophthalmological symptoms, observed during the preoperative period in children with craniopharyngioma (CPH). Material and methods: The study group comprised 20 children with CPH operated on at the Department of Neurosurgery, Polish Mother\'s Memorial Hospital-Research Institute in Lodz during the years 1990-2003. Medical records of the involved patients and laboratory tests results were the subject of a thorough analysis. Results: Endocrine disorders occurred in 13 out of 20 patients, most often: short stature (9/20), obesity (6/20), delay of puberty (5/20) and diabetes insipidus (2/20). The functional status of the thyroid gland and of the adrenal cortex was evaluated in 7 patients only, finding secondary hypothyroidism in 5 and secondary adrenocortical insufficiency in 4. General symptoms included: headaches (13/20), vomiting (5/20), behavioural changes (4/20). Ophthalmological symptoms included: restricted visual field (6/20), changes at the fundus of the eye (8/20) and deteriorated visual acuity (8/20). Neurological symptoms included: cranial nerves paresies (10/20), gait and balance disturbances (2/20), hemiparesis (3/20). Conclusions: 1. In the preoperative period, a considerable number of children with CPH, reveal functional disorders of the pituitary, manifested by growth retardation, secondary hypothyroidism and adrenocortical insufficiency. 2. The hormonal evaluation, especially of the thyroid gland and adrenal cortex, should routinely be performed in children with CPH before the surgery, due to the necessity of an appropriate hormonal replacement therapy in cases of secondary hypothyroidism and/or hypoadrenia.